The impact of initial antibiotic treatment failure: real-world insights in patients with complicated, health care-associated intra-abdominal infection - Peeters P (Infection and Drug Resistance, 2019)
Pascale Peeters,1 Kellie Ryan,2 Sudeep Karve,2 Danielle Potter,3 Elisa Baelen,4 Sonia Rojas-Farreras,5 Jesús Rodríguez-Baño6 1Real-World Insights, IQVIA, Saint-Ouen, France; 2Health Economics and Outcomes Research, AstraZeneca, Gaithersburg, MD, USA; 3Medical Evidence and Observational Research Center, AstraZeneca, Gaithersburg, MD, USA; 4Real-World Insights, IQVIA, St Prex, Switzerland; 5Real-World Insights, IQVIA, Barcelona, Spain; 6Department of Medicine, Unidad Clínica de Enfermedades Infecciosas, Microbiología y Medicina Preventiva, Hospital Universitario Virgen Macarena – Instituto de Biomedicina de Sevilla (IBiS), Universidad de Sevilla, Seville, Spain Purpose: The RECOMMEND study (NCT02364284; D4280R00005) assessed the clinical management patterns and treatment outcomes associated with initial antibiotic therapy (IAT; antibiotics administered ≤48 hours post-initiation of antibiotic therapy) for health care-associated infections across five countries.Patients and methods: Data were collected from a retrospective chart review of patients aged ≥18 years with health care-associated complicated intra-abdominal infection (cIAI). Potential risk factors for IAT failure were identified using logistic regression analyses.Results: Of 385 patients with complete IAT data, bacterial pathogens were identified in 270 (70.1%), including Gram-negative isolates in 221 (81.9%) and Gram-positive isolates in 92 (34.1%). Multidrug-resistant (MDR) pathogens were identified in 112 patients (41.5% of patients with a pathogen identified). IAT failure rate was 68.3% and in-hospital mortality rate was 40.8%. Multivariate regression analysis demonstrated three factors to be significantly associated with IAT failure: patients admitted/transferred to the intensive care unit during index hospitalization, isolation of an MDR pathogen and previous treatment with β-lactam antibiotics.Conclusion: We reveal the real-world insights into the high rates of IAT failure and mortality observed among patients with cIAI. These data highlight the challenges associated with choosing IAT, the impact of MDR pathogens on IAT outcomes and the importance of tailoring IAT selection to account for local epidemiology and patient history. Keywords: complicated intra-abdominal infection, health care associated, initial antibiotic treatment, clinical outcome, real-world treatment patterns